Invertebrate traits, diversity and the vulnerability of groundwater ecosystems. (30th July 2022) - Hose, Grant C.; Chariton, Anthony A.; Daam, Michiel A.; Di Lorenzo, Tiziana; Galassi, Diana Maria Paola; Halse, Stuart A.; Reboleira, Ana Sofia P. S.; Robertson, Anne L.; Schmidt, Susanne I.; Korbel, Kathryn L.
Abstract: Groundwater comprises the largest freshwater ecosystem on the planet. It has a distinct regime of extreme, yet stable environmental conditions that have favoured the development of similar morphological and functional traits in the resident invertebrate fauna (stygofauna). The analysis of community traits is increasingly used as an alternative to taxonomy‐based assessments of biodiversity, especially for monitoring ecosystem status and linking the functions of organisms to ecological processes, yet it has been rarely applied to stygofauna and groundwater ecosystems. In this paper, we review the variation in functional traits among the invertebrate fauna of this important ecosystem. We focus on the stygofauna and processes of alluvium and fractured rock aquifers that are typified by small voids and fissures that constrain the habitats and environmental conditions. As a first step, we compare trait variability between groundwater and surface water invertebrate communities and then examine the significance of the ranges of these traits to the vulnerability of the ecosystem to change. Fifteen potentially useful functional traits are recognised. Eight of these have narrower ranges (i.e. exhibit fewer states, or attributes, of a particular trait) in groundwater than they do in surface water. Two traits have wider ranges. Our synthesis suggests that the relative stability of groundwater environments has led to low trait variability. The low biomass and low reproductive rate of stygofauna suggest that recovery potential following disturbance is likely to be low. For the purposes of both improved understanding and effective management, further work is needed to document additional functional traits and their states in groundwater fauna, enabling a better understanding of the relationship between response and effect traits in these ecosystems. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Riassunto: Le acque sotterranee rappresentano il più vasto ecosistema di acqua dolce del pianeta. Esse sono caratterizzate da un regime peculiare di condizioni ambientali, per molti versi estreme ma stabili, che hanno favorito lo sviluppo di tratti morfologici e funzionali condivisi dalla maggior parte della fauna invertebrata che vi risiede. Gli approcci funzionali allo studio della biodiversità sono utilizzati sempre più di frequente in alternativa a quelli tassonomici, in particolare per monitorare lo stato degli ecosistemi e mettere in relazione le funzioni degli organismi con i processi ecologici. Tuttavia, essi sono stati applicati raramente agli ecosistemi delle acque sotterranee. In questo lavoro, abbiamo esaminato la variazione dei tratti funzionali della fauna invertebrata di questo importante ecosistema. Speciale attenzione è stata posta sulla fauna e sui processi ecologici negli acquiferi alluvionali e negli acquiferi litoidi fratturati che sono caratterizzati da vuoti e fessure di ridotte dimensioni che determinano la struttura degli habitat e le condizioni ambientali. In primo luogo, abbiamo confrontato la variabilità dei tratti funzionali delle comunità di invertebrati delle acque sotterranee rispetto alla fauna delle acque superficiali. Successivamente, abbiamo esaminato l'entità di tale variabilità in relazione alla suscettibilità dell'ecosistema acquatico sotterraneo alle variazioni ambientali. Abbiamo evidenziato dieci tratti funzionali potenzialmente utili, otto dei quali hanno intervalli di variazione più ristretti (cioè, sono caratterizzati da un numero ridotto di stati o modalità) nelle acque sotterranee rispetto alle acque superficiali. Due tratti hanno mostrato variazioni più ampie. I risultati del nostro lavoro suggeriscono che la relativa stabilità ambientale delle acque sotterranee ha determinato una ridotta variabilità di tratti funzionali. L'esigua biomassa e i bassi tassi riproduttivi della fauna delle acque sotterranee fanno presumere che il potenziale di recupero degli ecosistemi acquatici sotterranei a seguito di un disturbo ambientale sia limitato. Al fine di incrementare la conoscenza e la gestione efficace degli ecosistemi acquatici sotterranei, sono necessari nuovi studi volti ad indagare ulteriori tratti funzionali e le loro modalità. Questo consentirà una comprensione migliore della relazione tra tratti di risposta e tratti di effetto in tali ecosistemi. Read the free Plain Language Summary for this article on the Journal blog.